2018
DOI: 10.5935/1518-0557.20180023
|View full text |Cite
|
Sign up to set email alerts
|

Wistar rats immature testicular tissue vitrification and heterotopic grafting

Abstract: ObjectiveTo evaluate the efficiency of two vitrification protocols for rat immature testicular tissue and heterotopic transplantation.MethodsTwenty-four pre-pubertal Wistar rats were divided into three groups (n=8). After orchiectomy, testicular fragments (3mm) from Groups 1 and 2 were vitrified with different cryoprotectant concentration solutions, using sterile inoculation loops as support. After warming up, the fragments were submitted to cell viability assessment by Trypan blue and histological evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The cryopreservation of stem cells and embryos has been successful (10,11). The cryopreservation of rat testicular tissue (12), rat, pig and human islet tissue (13)(14)(15)(16) and liver tissues of mice, rats, dogs, monkeys and humans has also been successful (17). Cryopreservation is not only conducive to the accumulation of donor tissue, but also significantly reduces its immunity (18).…”
Section: Discussionmentioning
confidence: 99%
“…The cryopreservation of stem cells and embryos has been successful (10,11). The cryopreservation of rat testicular tissue (12), rat, pig and human islet tissue (13)(14)(15)(16) and liver tissues of mice, rats, dogs, monkeys and humans has also been successful (17). Cryopreservation is not only conducive to the accumulation of donor tissue, but also significantly reduces its immunity (18).…”
Section: Discussionmentioning
confidence: 99%
“…To optimize the preservation of ITT, a thorough comparison between vitrification and CSF techniques was conducted in this study. Several studies have also suggested that vitrification with low-concentration cryoprotectants results in minimal damage to ITT and reduces the likelihood of harm [ 15 ]. Furthermore, various transplantation strategies exist for ITT transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Scientists recommend cryopreservation of testicular tissue prior to cytotoxic therapies for preserving fertility in pre-pubertal cancer patients. 10 In vitro maturation (IVM) of spermatogonial stem cells obtained from cryopreserved pre-pubertal testicular tissues via two-dimensional (2D) and three-dimensional (3D) culture systems is the best potential procedure for the generation of functional sperm. 11,12 2D culture systems cannot effectively simulate the organized structure of the testicular microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Organoid culture technology is a simple and effective strategy to recognize the unknown mechanisms responsible for SSCs proliferation and differentiation 7–9 . Scientists recommend cryopreservation of testicular tissue prior to cytotoxic therapies for preserving fertility in pre‐pubertal cancer patients 10 …”
Section: Introductionmentioning
confidence: 99%